Health Informatics: Building Capacity Worldwide. Editorial - Kulikowski, C. A.; Geissbuhler, Antoine (Yearbook of Medical Informatics, 2010)
Objectives: To provide an editorial introduction to the 2010 IMIA Yearbook of Medical Informatics with an overview of its contents and contributors.Methods: A brief overview of the main theme, and an outline of the purposes, contents, format, and acknowledgment of contributions for the 2010 IMIA Yearbook.Results: This 2010 issue of the IMIA Yearbook highlights important developments in the building of workforce capacity in medical informatics worldwide, covering activities in research, education and practice in this interdisciplinary field. Progress towards educating and keeping professionals in the field up-to-date is complemented by outreach to the wide range of disciplines and biomedical and health specialties that are covered by this very broad field, identified from the recent literature, illustrated by selected papers published during the past 12 months.xsConclusion: Reviews and Surveys of the main research sub-fields in biomedical informatics in the Yearbook provide an overview of progress and current challenges across the spectrum of the discipline.
Keywords: Editorial; 2010 IMIA Yearbook of Medical Informatics; surveys of biomedical informatics; reviews of biomedical informatics; history of biomedical informatics; IMIA and its societies